(untitled) (Indian Journal of Animal Production and Management, 2025)
In this study, the ratio of feed cost to production income was determined for carp polyculture systems in Tripura, India. Data was collected from experimental ponds over a 10-month culture period from May to February. Three different species compositions of Indian major carps were evaluated: Treatment 1 (Catla 40%, Rohu 30%, Mrigal 30%), Treatment 2 (Catla 30%, Rohu 40%, Mrigal 30%), and Treatment 3 (Catla 30%, Rohu 30%, Mrigal 40%). All ponds were stocked at a density of 7500 fingerlings per hectare in 200 m² experimental ponds with water depths of 1-1.5 m. Feed consumption, growth parameters, and economic indicators were monitored throughout the production cycle. Other operating costs during the production period (pond preparation, fingerlings, labor, equipment, depreciation, marketing, etc.) were excluded from the analysis. In carp polyculture, feed represents the highest share of total production costs during the growing period. According to the study results, the feed cost/production income ratio of Treatment 2 was the most favorable at 0.28, followed by Treatment 1 at 0.29, and Treatment 3 at 0.31. Production levels ranged from 4000-4090 kg/ha across treatments. Treatment 2 showed better economic performance due to the higher proportion of Rohu, which demonstrated superior feed conversion rates under the study conditions. The findings suggest that optimizing species composition in carp polyculture systems can improve economic returns by enhancing feed utilization efficiency.